1997
DOI: 10.1088/0954-3899/23/11/010
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold resonances in few-neutron systems

Abstract: Three-and four-neutron systems are studied within the framework of the hyperspherical approach with a local S-wave nn-potential. Possible bound and resonant states of these systems are sought as zeros of three-and fourbody Jost functions in the complex momentum plane. It is found that zeros closest to the origin correspond to sub-threshold (nnn) 1 2 − and (nnnn) 0 + resonant states. The positions of these zeros turned out to be sensitive to the choice of the nn-potential. For the Malfliet-Tjon potential they a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 18 publications
(50 reference statements)
5
60
1
Order By: Relevance
“…From such large values for the scattering length a(ηN), Haider and Liu [10] have shown that η can be bound in nuclei with A ≥ 12. Other groups have also found similar results [12,13,14,15].…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…From such large values for the scattering length a(ηN), Haider and Liu [10] have shown that η can be bound in nuclei with A ≥ 12. Other groups have also found similar results [12,13,14,15].…”
Section: Introductionsupporting
confidence: 70%
“…[44], [45], [14] bound states in light nuclei were calculated by the finite rank approximation (FRA). Within this approximation the motion of the η and of the nucleons inside the nucleus are treated separately.…”
Section: The η Nucleus Potential and Search For Quasi Bound Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…The only rigorous study of tetraneutron resonances was accomplished in ref. [10] using the simplistic MT I-III nn interaction, which contains only S -waves. Unfortunately no observable resonances have been found there and only the existence of some broad subthreshold structures (S-matrix poles with negative real energy parts) was pointed out.…”
Section: Introductionmentioning
confidence: 99%